The boy who came up quietly - Capizzi, Michael; Colton, Keita (New York World Publishing, 1971)
A quiet boy becomes friends with the Wind and his sons, the four princes who rule the seasons.
Keywords: Seasons -- Fiction -- Juvenile fiction